1997
DOI: 10.1136/hrt.77.6.558
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic Doppler echocardiographic analysis of phasic coronary blood flow velocity in hypertrophic cardiomyopathy.

Abstract: Objective-To use transthoracic Doppler echocardiography to assess coronary blood flow non-invasively in patients with hypertrophic cardiomyopathy. Design-High frequency transthoracic Doppler echocardiography was used to assess resting phasic coronary velocity patterns in patients with hypertrophic cardiomyopathy and to define the relation between coronary flow patterns and clinical, echocardiographic, and haemodynamic manifestations of this condition. Patients with hypertrophic cardiomyopathy commonly have evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 37 publications
(5 reference statements)
0
16
0
Order By: Relevance
“…With regard to CFtvi, Crowley et al [24] showed no difference in CFtvi between HCMP patients and normal subjects. However, in our study, baseline CFtvi was also significantly higher in HCMP patients than in normal subjects.…”
Section: Discussionmentioning
confidence: 97%
“…With regard to CFtvi, Crowley et al [24] showed no difference in CFtvi between HCMP patients and normal subjects. However, in our study, baseline CFtvi was also significantly higher in HCMP patients than in normal subjects.…”
Section: Discussionmentioning
confidence: 97%
“…The distal LAD flow velocities we measured noninvasively with transthoracic echocardiography parallel closely the results of other investigators. 6,12,13 Other investigators have found that in proximal parts of the coronary arteries measured semi-invasively with transesophageal echocardiography, flow velocities vary from 0.34 ± 0.08 m/s to 0.81 ± 0.1 m/s. 14,15 In by far the largest group of patients scheduled for coronary angiography, Kasprzak et al 16 reported values for the LM (0.72 ± 0.21 m/s), proximal LAD (0.69 ± 0.27 m/s), and proximal Cx (0.77 ± 0.27 m/s) that agree well with our results.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that the LAD flow velocity pattern during diastole in patients with HCM is characterized by slow acceleration during early diastole [6][7][8][9] and rapid deceleration after the peak velocity [7]. The former characteristic finding may be due to the slow acceleration of the diastolic pressure gradient curve between the aorta and the LV caused by the slower downslope of the LV pressure curve reflecting the disturbance of early diastolic relaxation.…”
Section: Discussionmentioning
confidence: 96%
“…The flow velocity pattern of the LAD in patients with hypertrophic cardiomyopathy (HCM) is characterized by decreased or retrograde systolic flow and the slow acceleration of diastolic flow [6][7][8][9]. In patients with hypertensive left ventricular hypertrophy (LVH), however, the characteristics of the LAD flow velocity pattern and the difference from that in HCM have not been fully investigated [10].…”
Section: Introductionmentioning
confidence: 99%